ANALISIS KEPUTUSAN PEMBELIAN PADA DISTRO BLOOD BOUND - Muchamad Ilham Nazarudin; Supriyono (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the influence of price perception and product quality on purchase decisions at Distro Blood bounD in Porong, Sidoarjo. A quantitative approach was applied, utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS) for data analysis. Data were collected through questionnaires distributed to 98 respondents selected using non-probability sampling with an accidental sampling technique. The research instrument was developed based on indicators of each variable and measured using a five-point Likert scale. The findings indicate that both price perception and product quality have a positive and significant effect on purchase decisions. These results highlight the importance of maintaining stable pricing strategies and offering high-performance products to influence consumer purchasing behavior